Development and structural change in Asia-Pacific : globalising miracles or end of a model? - Andersson, Martin, 1969-; Gunnarsson, Christer, 1948- (RoutledgeCurzon, 2003)
Annotation The authors consider how the Asia-Pacific economies have developed since the financial crises and highlight two inter-related themes: the effect of global forces on the national Asian economies and the different development paths of these economies as they jointly enter this new phase. Questions raised by the book include: * is globalization a threat to development and prosperity in the Asia-Pacific or did globalization rather facilitate and accelerate the pace of industrialization among late industrializers in the region? * is there a single Asia-Pacific development model or did the crisis show this to be false? * did the financial crisis reveal structural weaknesses in an Asia-Pacific state-led model or was state leadership already in demise? Development and Structural Change in Asia-Pacificprovides a useful and relevant account of how the global economy has led to structural changes within Asian economies
Keywords: Structural adjustment (Economic policy) -- East Asia.; Globalization.; East Asia -- Economic conditions.; Mondialisation.; Extrême-Orient -- Conditions économiques.; globalism.; POLITICAL SCIENCE -- Public Policy -- Economic Policy.; BUSINESS & ECONOMICS -- Government & Business.; BUSINESS & ECONOMICS -- Development -- Economic Development.; BUSINESS & ECONOMICS -- Development -- Business Development.; BUSINESS & ECONOMICS -- Structural Adjustment.; BUSINESS & ECONOMICS -- Development -- General.; Economic history; Globalization; Structural adjustment (Economic policy); East Asia; Wirtschaftsentwicklung; Strukturwandel; Wirtschaftliche Lage; Globalisierung; Asiatisch-Pazifischer Raum; Ajustement structurel -- Asie orientale.; Ajustement structurel (politique économique) -- Asie orientale.; Asie orientale -- Conditions économiques.